Kolportaż druków muzycznych przez Drukarnię W. Deckera w świetle anonsów prasowych i jego wpływ na kształtowanie kultury muzycznej Wielkopolan - Jazdon, Artur; Jazdon, Andrzej (Biblioteka Uniwersytecka w Poznaniu, 2013)
Drukarnia W. Deckera była bardzo znanym zakładem typograficznym w Poznaniu okresu zaborów. W artykule omówiono pomijaną dotychczas jej działalność księgarską. Obejmowała ona kolportaż druków muzycznych sprowadzanych głównie z Lipska. Badając ten problem, przeprowadzono kwerendę prasową, która dała dość zaskakujące wyniki. Odkryto nieznane do tej pory, samoistne, obszerne katalogi księgarskie. Zawierają one informacje o drukach muzycznych dostępnych w sprzedaży. Zestaw oferowanych nut był bardzo duży. Począwszy od druków pedagogicznych, poprzez nuty przeznaczone dla amatorów, po partytury dla zespołów zawodowych. Wśród proponowanych utworów przeważają dzieła najnowsze, skomponowane po roku 1800. Mimo iż większość nazwisk występujących w katalogach nie jest dzisiaj znana publiczności, poszczególne spisy przekazują informacje o muzyce wartościowej. Wiele dzieł odegrało rolę w rozwoju muzyki i kształtowaniu gustów muzycznych Wielkopolan.

The W. Decker printing shop was a well-known typographical establishment in Poznań at the time of the partitions. The article discusses the book trade of the output of this private press, an issue that hitherto has not been addressed adequately. This activity involved circulation of musical prints imported mainly from Leipzig. While investigating this particular issue and following a press query, the authors came to a quite a surprising conclusion. The press query has made it possible to discover autonomous and extensive book trade catalogues so far unknown. The catalogues in question provide us with information on musical prints available at the time. The wide variety of music styles offered by the printing shop was extensive and covered educational material, sheet music for the exclusive non-professional use and, finally, musical scores for professional ensembles. The offered musical pieces include in the main the then latest works, i.e., those composed after the year 1800. Though the majority of the names represented in the catalogues is not known to the general public today, individual catalogues provide us with much valuable information on music of some merit. Many of these compositions have been forgotten irrevocably, but they undoubtedly had their share in the general development of music and the development of musical tastes of the inhabitants of the Wielkopolska region.
The distribution system of musical prints and scores in W. Decker printing shop in view of the press advertisements at the time and its influence upon the shaping process of musical culture of the inhabitants of Greater Poland
Keywords: księgarstwo XIX wiek; Drukarnia W. Deckera; kultura muzyczna Poznania w pierwszej połowie XIX wieku; handel muzykaliami; book trade in the 19th c.; W. Decker printing shop; musical culture in Poznań of the first half of the 19th c.; sheet music trade